Exploring the Role of Laryngopharyngeal Reflux in Eustachian Tube Dysfunction: Therapeutic Potential of Proton Pump Inhibitors in a Resource-Constrained Setting - Ahmad, Muhammad Tehseen; Farooq, Umer; Akram, Arslan; Naqvi, Syeda Hadia Batool; Maheen, Maimoona; Haider, Ali; Nashwan, Abdulqadir J; Maqbool, Shahzaib; Rehman, Abdur (Curēus (Palo Alto, CA), 2025)
Background Eustachian tube dysfunction (ETD) and laryngopharyngeal reflux disease (LPRD) are under-recognized conditions that significantly impact quality of life. LPRD may contribute to ETD via gastric refluxate-induced mucosal damage. While proton pump inhibitors (PPIs) are commonly used for reflux management, their role in alleviating ETD symptoms remains controversial. This study investigates the association between LPRD and ETD and evaluates the efficacy of PPI therapy in ETD management. Methods A prospective study was conducted on patients diagnosed with ETD and LPRD. A total of 126 patients were included using consecutive non-randomized sampling. The participants underwent an eight-week regimen of twice-daily 40 mg oral omeprazole. ETD severity was assessed using the Eustachian Tube Dysfunction Questionnaire (ETDQ-7), while LPRD severity was measured via the Reflux Symptom Index (RSI) and Reflux Finding Score (RFS), both pre- and post-intervention. Independent t-tests and correlation analyses were performed to evaluate treatment outcomes. Results Significant reductions were observed in ETDQ-7 (16.20±10.47 to 10.40±5.47, p<0.001), RSI (11.42±7.65 to 4.50±2.65, p<0.001), and RFS (22.56±10.14 to 4.84±2.45, p<0.001) scores following PPI therapy, suggesting symptomatic improvement in both ETD and LPRD. Correlation analysis revealed a moderate association between both ETDQ-7 and RSI (0.346-0.391, p<0.001), and ETDQ-7 and RFS (0.437-0.515, p<0.001) scores respectively. However, residual symptoms in some patients suggest that additional pathophysiological factors may contribute to ETD beyond the reflux-mediated inflammation. Conclusion This study provides evidence supporting the link between LPRD and ETD and suggests that PPI therapy may alleviate ETD symptoms in a subset of patients. However, given the multifactorial nature of ETD, further studies are needed to explore alternative therapies (such as potassium channel blockers, Eustachian tube dilation, etc.) and long-term treatment outcomes.